Genetic and biochemical characterization of D-arabinose dehydrogenase from Neurospora crassa. - Carrasco, A (1981)
D-Arabinose dehydrogenase has been purified to homogeneity from wild-type Neurospora crassa 74-A (FGSC 262) and from two colonial mutants, col-15a (FGSC 1391) and col-16a (FGSC 1349), found to contain more of the enzyme. The enzymes were characterized by measurement of several kinetic and physicochemical parameters. The enzymes were the same in all characteristics studied thus far. Immunological studied performed with enzyme preparations from the three strains showed antigenic identity and indicated that those colonial strains contain more normal enzyme, rather than the usual amount of an altered "improved" enzyme. Quantitation of the enzyme in crude extracts, performed by single radial immunodiffusion, showed that the colonial strains have twice the level of enzyme as the wild-type strain. Genetic characterization, performed by analysis of meiotic products, heterokaryosis, and reversions, indicated that the difference in D-arabinose dehydrogenase activity detected among the three strains is probably determined by one gene. The genetic control, structural or regulatory of this enzyme activity is different from that determining the morphological alterations exhibited by mutant strains carrying the col-15 or col-16 gene.